ON SOME ČEBYŠEV-GRÜSS TYPE INTEGRAL INEQUALITIE - Aglić Aljinović, Andrea; Hoxha, Razim; Pečarić, Josip (Matematichki Bilten, 2006)
In this paper we establish some Čebyšev–Grüss type integral inequalities, by using the extension of the Montgomery identity.